Gestational Age-Dependent Increase of Survival Motor Neuron Protein in Umbilical Cord-Derived Mesenchymal Stem Cells - Sota Iwatani; Nur Imma Fatimah Harahap; Dian Kesumapramudya Nurputra; Shinya Tairaku; Akemi Shono; Daisuke Kurokawa; Keiji Yamana; Khin Kyae Mon Thwin; Makiko Yoshida; Masami Mizobuchi; Tsubasa Koda; Kazumichi Fujioka; et al. (Frontiers Media S.A., 2017)
BackgroundSpinal muscular atrophy (SMA) is the most common genetic neurological disease leading to infant death. It is caused by loss of survival motor neuron (SMN) 1 gene and subsequent reduction of SMN protein in motor neurons. Because SMN is ubiquitously expressed and functionally linked to general RNA metabolism pathway, fibroblasts (FBs) are most widely used for the assessment of SMN expression in SMA patients but usually isolated from skin biopsy samples after the onset of overt symptoms. Although recent translational studies of SMN-targeted therapies have revealed the very limited time window for effective SMA therapies during perinatal period, the exact time point when SMN shortage became evident is unknown in human samples. In this study, we analyzed SMN mRNA and protein expression during perinatal period by using umbilical cord-derived mesenchymal stem cells (UC-MSCs) obtained from preterm and term infants.MethodsUC-MSCs were isolated from 16 control infants delivered at 22-40 weeks of gestation and SMA fetus aborted at 19 weeks of gestation (UC-MSC-Control and UC-MSC-SMA). FBs were isolated from control volunteer and SMA patient (FB-Control and FB-SMA). SMN mRNA and protein expression in UC-MSCs and FBs was determined by RT-qPCR and Western blot.ResultsUC-MSC-Control and UC-MSC-SMA expressed the comparable level of MSC markers on their cell surface and were able to differentiate into adipocytes, osteocytes, and chondrocytes. At steady state, SMN mRNA and protein expression was decreased in UC-MSC-SMA compared to UC-MSC-Control, as observed in FB-SMA and FB-Control. In response to histone deacetylase inhibitor valproic acid, SMN mRNA and protein expression in UC-MSC-SMA and FB-SMA was increased. During perinatal development from 22 to 40 weeks of gestation, SMN mRNA and protein expression in UC-MSC-Control was positively correlated with gestational age.ConclusionUC-MSCs isolated from 17 fetus/infant of 19-40 weeks of gestation are expressed functional SMN mRNA and protein. SMN mRNA and protein expression in UC-MSCs is increased with gestational age during perinatal development.